2015
DOI: 10.1111/jnc.13108
|View full text |Cite
|
Sign up to set email alerts
|

Development of mature BDNF‐specific sandwich ELISA

Abstract: Mature brain-derived neurotrophic factor (mBDNF) plays a vital role in the nervous system, whereas proBDNF elicits neurodegeneration and neuronal apoptosis. Although current enzymelinked immunosorbent assay (ELISA) has been widely used to measure BDNF levels, it cannot differentiate mBDNF from proBDNF. As the function of proBDNF differs from mBDNF, it is necessary to establish an ELISA assay specific for the detection of mBDNF. Therefore, we aimed to establish a new mBDNF-specific sandwich ELISA. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 35 publications
(67 reference statements)
0
27
0
1
Order By: Relevance
“…The manufacturer of the ELISA kit we use claims 13% cross-reactivity for recombinant human pro-BDNF. The Elisa kit we used has a very low cross-reactivity for proBDNF compared to the other available ELISA kits (see Polacchini et al [55] and Lim et al [56]),…”
Section: Methodsmentioning
confidence: 99%
“…The manufacturer of the ELISA kit we use claims 13% cross-reactivity for recombinant human pro-BDNF. The Elisa kit we used has a very low cross-reactivity for proBDNF compared to the other available ELISA kits (see Polacchini et al [55] and Lim et al [56]),…”
Section: Methodsmentioning
confidence: 99%
“…Mature BDNF ELISA and proBDNF ELISA was performed according to Dr. Zhou's published paper before. 23…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%
“…injected with one single dose of sheep anti-proBDNF (Fan et al, 2008;Lim et al, 2015) antibody (10 μg,1 μg/μl) on day 22 with a Hamilton syringe, and then behaviorally assessed on days 23, 24, and 25 ( Figure 3a); (2) i.p. injected with one dose of anti-proBDNF antibody (10 μl, 0.08 μg/μl per g of body weight) on day 22, followed by one half the dose on day 26, and behaviorally assessed on days 27, 28, and 29 ( Figure 3a); and (3) i.m.…”
Section: Animal Surgery and Microinjectionmentioning
confidence: 99%
“…However, AAV-proBDNF increased the depression-like behavior as indicated by a significant increase in the percentage of immobility in the forced swimming test (two-way ANOVA, injection factor: F (1,10) = 0.38, p = 0.544; proBDNF factor: F (1,10) = 5.58, p = 0.028; injection × proBDNF: F (1,10) = 2.62, p = 0.121; Figure 6e). To check the efficacy of AAV-proBDNF treatment to increase proBDNF levels in the brain, we performed an ELISA assay as previously described (Lim et al, 2015) and found that proBDNF levels were significantly increased in the neocortex (Student's t-test, t (10) = − 13.54, po0.001; Figure 6f) and cerebellum (Student's t-test, t (10) = − 2.81, p = 0.019; Figure 6f) but not in hippocampus (Student's t-test, t (10) = − 1.69, p = 0.121; Figure 6f). Histological examination showed that green fluorescence was detected in the brains of rats that received AAV-EGFP but not AAV-proBDNF, and a significant upregulation of proBDNF expression was detected in the brains of rats that received AAV-proBDNF but not AAV-EGFP (Figure 6g).…”
Section: Brain Injection Of Aav-probdnf Increased Depression-like Behmentioning
confidence: 99%
See 1 more Smart Citation